Collocation productions by Myanmar refugee learners in Malaysia / Kannigaa Markundu - Kannigaa , Markundu (2019)
Collocations are very crucial for language comprehension and fluency. According to Hill (2000) second language learners make mistake not because of grammar but due to deficiency in collocational knowledge. Hong (2012) stresses that teaching of vocabulary focus on single word learning which mostly neglects collocation. Similar condition can be observed in our national school context as grammar teaching is emphasized thus neglecting the inclusion of phraseology (Normazidah Che Musa, Koo & Hazita Azam, 2012). Focus on collocations can lead to successful language learning for all learners irrespective of their level of proficiency. However, studies focusing on collocational knowledge of refugee learners in Malaysia are very rare especially those related to refugees in Malaysia. Refugees in Malaysia find it hard to survive and are denied access to formal education (http://www.unchr.org.my). Therefore, they largely depend on schools run by NGOs and „hidden schools‟ by their own community (Zarkesh, Baranovich & Shoup, 2017).Upon resettling in countries like America, the young refugee learners face a state of helplessness because they could not perform well in academics, particularly their writing skills are very poor (Hirano, 2014). Due to this lack of attention paid to this group of learners, the study aims to investigate the types of lexical collocations produced by Form 3 Myanmar Refugee learners in their picture based essay writing. Additionally study also describes the possible sources for the production of deviant lexical collocations. The subjects of this study were 30 Form 3 Myanmar refugee learners from 4 different ethnic backgrounds namely Burmese, Zomi, Hakha and Myanmar Tamil. 30 essay samples were analyzed in this study. The participants were selected from a population of Myanmar learners consisting of 40 learners. 30 essay samples were manually reviewed and analyzed to identify lexical collocations. The lexical collocations were identified and classified based on Hsu‟s Framework of Classification of Lexical Collocations 2007. Researcher used British National Corpus, BBI Combinatory Dictionary 1998 and Oxford Collocations Dictionary 2002 to determine the acceptability of lexical collocation (Wong, 2014; Ahmadi, 2012; Sadegi, 2011). To further confirm a deviant collocation, Modified Framework of Types of Lexical Collocational Errors was used. After the identification of deviant collocations, the researcher used Modified Framework of Possible Sources of Lexical Collocational Errors to analyze the deviant collocations produced by the participants of the research. Analysis revealed that participants recorded a total of 239 lexical collocations, among them 63 (26.4%) were deviant lexical collocations. The most frequent lexical collocation used in the written task is L2 (Adjective + Noun) type. The most problematic lexical collocation type is L3 (Noun +Verb) type as 60% of it were deviant collocations. Use of synonym was identified as the main source of lexical collocational errors to occur in the participants‟ written task. Thus, the findings of the research indicate the need to incorporate collocational teaching for all learners. Current study recommends employment of refugee participants representing countries other than Myanmar.